Evaluation of no-choice cage, detached leaf and diet incorporation assays to screen chickpeas for resistance to the beet armyworm Spodoptera exigua (Lepidoptera: Noctuidae). (March 2014) - Shankar, M.; Sharma, H.C.; Ramesh Babu, T.; Sridevi, D.
<x content-type="archive" xml:space="preserve">Abstract</x> It i.s difficult to compare genotypic resistance to insects across seasons and locations because of the variation in the onset and severity of insect infestation. Therefore, in this study, we used the no-choice cage technique and detached leaf and artificial diet incorporation assays for evaluating chickpea genotypes for resistance to the beet armyworm Spodopteraexigua (Hubner). The results indicated that the no-choice cage technique was not useful for evaluating chickpea genotypes for resistance to S. exigua. In the detached leaf assay, leaf feeding by S. exigua larvae was significantly lower in ICC 12 475 and RIL 20 genotypes at the vegetative stage and in ICC 10 393, ICC 12 475, KAK 2, RIL 20 and RIL 25 genotypes at the flowering stage, while larval weight gain was lower in insects reared on EC 583264, ICC 10 393, ICC 12 475 and RIL 20 genotypes at the vegetative stage; and in those reared on ICC 10 393, ICC 12 475, EC 583264, ICCL 86 111, KAK 2, RIL 20 and RIL 25 genotypes at the flowering stage in plants raised under greenhouse conditions. In plants raised under field conditions, the EC 583260, ICC 12 475, ICCL 86 111, ICCV 10, KAK 2, RIL 20 and RIL 25 genotypes in the November sowing and the KAK 2, ICC 3137, ICCL 86 111 and RIL 25 genotypes in the December sowing suffered low leaf damage at the vegetative stage; and EC 58 320, EC 583264, ICC 12 745 and RIL 25 genotypes in the November sowing and the EC 583264, ICC 3137, ICC 12 475, 1CCL 86 111, KAK 2, RIL 20 and RIL 25 genotypes in the December sowing suffered low leaf damage at the flowering stage, while low larval weights were recorded in insects reared on the ICC 12 475, EC 583264, ICCL 86 111 and RIL 25 genotypes at the flowering stage. In the diet incorporation assay, the survival of S. exigua larvae reared on diets with leaf powder of the ICC 12 475, ICC 10 393 and RIL 25 genotypes was significantly lower, while a significant reduction in larval weights was recorded in those reared on diets with leaf powder of the ICC 10 393, ICC 12 475, ICCL 86 111, KAK 2, RIL 25 and ICC 3137 genotypes. The fecundity of insects was also reduced in insects reared on diets with leaf powder of the RIL 25, RIL 20, ICCV 10, ICCL 86 111, ICC 12 475, ICC 3137, KAK 2 and ICC 10 393 genotypes. The results suggest that detached leaf assay could be used for large-scale screening of chickpea genotypes for resistance to S. exigua, while the diet incorporation assay could be used to gain additional information on the antibiosis mechanism of resistance to this insect.